MATERNAL MORTALITY: A TEN YEAR REVIEW IN A TERTIARY CARE SETUP - Khan, Bushra; Deeba, Farhat; Khattak, Samina Naseem (Journal of Ayub Medical College Abbottabad, 2012)
Background: Maternal mortality ratio of a country is indicative of its health and development status. Information on maternal mortality is required to determine this status and to set priorities for policy making and programmatic and operation research strategies. This study was conducted to determine the causes of maternal mortality in a tertiary care hospital. Methods: This study was conducted in Department of Obstetrics & Gynaecology B Unit, Ayub Medical College, Abbottabad, from January 2002 to January 2012. Data of all the pregnant patients admitted to Obs/Gyn Unit '˜B' Labour Room were retrospectively collected and reviewed for the causes of direct maternal deaths. Results: There were 21,120 deliveries during the study period. Out of these, there were 163 maternal deaths. The maternal mortality ratio was calculated as 772 per 100,000 live births. Direct maternal deaths constituted 143 (87.7%) and indirect deaths were responsible for 20 (12.3%) deaths. Haemorrhage was the leading cause of maternal death and was responsible for 43.55% of maternal deaths, while eclampsia was observed in 26.99% of maternal deaths. In 6.13% of patients rupture uterus was the cause of maternal death. Conclusion: Maternal mortality in our part of the world is high and most of the causes of maternal death remain haemorrhage and eclampsia. Haemorrhage which is the leading cause of maternal death is both predictable and preventable, if proper peripartum care is provided, maternal mortality can be reduced. Keywords: Maternal mortality, Eclampsia, Septicaemia, Haemorrhage, Pulmonary embolism